'Our lives is in danger': Manus Island and the end of asylum. (October 2017) - Grewcock, Michael
The Australian-funded and operated immigration detention centre on Manus Island, Papua New Guinea, serves as a frontline for Australia's border policing measures against unauthorised refugees. The willingness of the Australian state to forcibly transfer and detain refugees at sites such as Manus Island reflects its commitment to deterring unauthorised arrivals by punishing them for their methods of travel. Comparing the outcomes of the 2016 refugee global summits and recent public inquiries into the conditions on Manus Island, this article considers the disconnect between Australia's criminogenic border policing practices and its supposed commitments to a humanitarian refugee resettlement policy. It argues that the dominant view of resettlement as an outcome to be bestowed on 'worthy' refugees removes refugee agency and enables ongoing and systemic human rights abuses at sites such as Manus Island. For refugees this can only be resolved by establishing a right to free movement.